PERBANDINGAN METODE MOVING AVERAGE, EXPONENTIAL SMOOTHING DAN EXPONENTIAL SMOOTHING WITH TREND DALAM PERAMALAN KEBUTUHAN MATERIAL CV KARYA TEKNIK MANDIRI - Setyawan, Mega; Ismiyah, Elly; Dhartikasari, Efta (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
Using historical data, forecasting is a technique for estimating future values. The CV Karya Teknik Mandiri was the site of this study. Buildings in industries, civil workers, backfilling, bridges, cementing/irrigation, mechanical & electrical workers, plumbing, electrical installations, ducting/ac, and other services are all provided by CV Karya Teknik Mandiri. Material buildup occurs often at CV Karya Teknik Mandiri. Material buildup at CV Karya Teknik Mandiri leads to losses, including unnecessary storage space usage and a higher risk of material deterioration, which lowers the caliber of produced items. This study examines the comparison of moving average methods, exponential smoothing, and exponential smoothing with trend in forecasting material needs, particularly cement at CV Karya Teknik Mandiri, as the company must make precise projections for material needs in the coming months. The Exponential Smoothing approach with α = 0.5 has a lower error rate than other approaches, according to data gathering and processing. The Exponential Smoothing technique with α = 0.5 gets a rating of 19.646 (Bias). MAPE 52.132%, MAD 312.391, MSE 179758.9, and standard error 434.715. The chosen approach is Exponential Smoothing α = 0.5, it may be concluded. The quantity of Material Demand (Cement) that CV Karya Teknik Mandiri is expected to have in July 2021 is 865 / (sack / 50 kg), according to the study of the forecast.